2007
DOI: 10.1177/1933719107306228
|View full text |Cite
|
Sign up to set email alerts
|

Disordered Meiotic Regulation of Oocytes by Duration of Diabetes Mellitus in BBdp Rat

Abstract: Diabetes mellitus (DM) disturbs normal functions from the level of cells to the level of organs. In this study, the authors explore the detrimental effects of type 1 diabetes on meiotic regulation depending on the duration of DM. In non-diabetes-prone BioBreeding (BBdr) control rats, most of the large follicles had germinal vesicle (GV)-intact oocytes. Conversely, a decrease of intact GV that was dependent on the duration of diabetic symptoms was observed; only 54% of the large follicles of diabetes-prone BB (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 30 publications
2
16
1
Order By: Relevance
“…Our results showed that insulin treatment could partly cure but not completely reverse the effects of diabetes on oocytes, which were contradictory to earlier studies (Colton et al 2002, Kim et al 2007). We speculate that there were two reasons for this contradiction.…”
Section: Discussioncontrasting
confidence: 57%
See 3 more Smart Citations
“…Our results showed that insulin treatment could partly cure but not completely reverse the effects of diabetes on oocytes, which were contradictory to earlier studies (Colton et al 2002, Kim et al 2007). We speculate that there were two reasons for this contradiction.…”
Section: Discussioncontrasting
confidence: 57%
“…The delay in oocyte meiotic maturation was improved with insulin treatment during superovulation (Colton et al 2002). Kim et al (2007) also observed that insulin reverses the diabetes effect on in vitro maturation effects of the chronic diabetes-prone BioBreeding rats. However, we found that the ovulation rate of mice with severe hypoglycemia was lower than that of controls after insulin treatment.…”
Section: Introductionmentioning
confidence: 77%
See 2 more Smart Citations
“…In addition, mouse oocytes from pre-ovulatory follicles are w30% smaller in size compared to oocytes from control animals (Chang et al 2005). Secondly, COCs from chemically induced diabetic mice exhibit aberrant nuclear maturation, with precocious resumption of meiosis during spontaneous maturation and decreased efficiency of induced maturation, leading to an MI-MII transition block in both models (Kim et al 2007). Poor nuclear maturation was attributed to decreased de novo purine and cAMP synthesis as a result of decreased flux of glucose through PPP (Colton et al 2003).…”
Section: Maternal Environment and Oocyte Developmental Competencementioning
confidence: 99%